2020
DOI: 10.1177/0002764220979777
|View full text |Cite
|
Sign up to set email alerts
|

What Does Rigged Mean? Partisan and Widely Shared Perceptions of Threats to Elections

Abstract: This article is a piece of a larger line of research supported by the Democracy Fund studying how to communicate about threats to elections in ways that do not dampen people’s desire to vote or make them question the integrity of electoral outcomes. It reports findings from a computerized text analysis of 2,970 open-ended survey responses in the field during the fall of 2018 to the prompt “when people say that elections are rigged, what do you think they mean?” Four key themes emerged in the data: (1) Democrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…When directly asked about their thoughts on money in politics, Americans across income levels believe money in politics is a source of power, inevitable, too influential, immoral, and an area in need of policy intervention (Park‐Ozee 2022). Other scholars find that, across parties, most Americans believe there is too much money in politics, that elected officials are bought off, and campaign donors are essentially paying bribes (Primo and Milyo 2020).…”
Section: Money and External Efficacymentioning
confidence: 99%
“…When directly asked about their thoughts on money in politics, Americans across income levels believe money in politics is a source of power, inevitable, too influential, immoral, and an area in need of policy intervention (Park‐Ozee 2022). Other scholars find that, across parties, most Americans believe there is too much money in politics, that elected officials are bought off, and campaign donors are essentially paying bribes (Primo and Milyo 2020).…”
Section: Money and External Efficacymentioning
confidence: 99%
“…Despite the predominance of the winner effect, ideology and partisanship still play at least two meaningful roles. First, the perceived source of distrust differs between the two sides, with liberals consistently more concerned about voter suppression by government officials (Avery, 2007; Bullock III et al, 2005; Carey et al, 2020), and conservatives more concerned about widespread voter fraud by ineligible voters (Berlinski et al, 2021; Park-Ozee 2021; Sheagley & Udani, 2021). Second, recent research has suggested that conservatives are more prone to conspiratorial thinking, both in response to specific events and as a general worldview (Edelson et al, 2017; Van der Linden and Jost 2021), which may generally predispose them more towards election distrust, towards taking action based on said distrust, and inoculate them against attempts by fact-checkers and experts to assuage their concerns.…”
Section: Literature Reviewmentioning
confidence: 99%